Interpretation of Characters in the Story of "Goodness" By Odil Yaqubov - Xolmatov Doston (Genius Journals, 2023)
The article examines the interpretation of heroes and characters in Odil Yaqubov's story "Goodness", and the ability to reflect the spirit of the time. Specific features of the writer's style are shown on the basis of examples.
Keywords: skill; style; period; character